ANTIMYCOTICACTIVITY OF AQUEOUS EXTRACT OF TAMARIXRAMOSISSIMA LEDEBBARKON IN VITRO AND IN VIVO GUINEA PIG MODEL OF DERMATOPHYTOSIS: Pharmaceutical Sciences-Medicine - ALI MIKAEILI; KARIMI, ISAAC; MODARRESI, MASOUD; SHAHBAZI, ATEFE; JALILIAN, NASTARAN (International Journal of Life Science and Pharma Research, 2018)
The decoction of the bark of different species of tamarisk is used as a remedy for the treatment of ringworm in sheep in Kurdish ethno medicine (Iran).The aim of this study was to evaluate the antifungal effects of the aqueous extract of TamarixramosissimaLedeb. (Tamaricaceae) barkagainst Epidermophytonfloccosum and Trichophytonverrucosum. The antifungal activity of aqueous extracts of both dried and burned barks were evaluated against E.floccosumand T.verrucosum by disc diffusion test and determination of minimum inhibitory concentrations (MICs).The dorsum of guinea pigs was infected with T.verrucosum conidia andthe animals topically treated as follows: negative control (NC) received normal saline solution plus distilled water; positive control (PC) received 1% terbinafine, while three other groups, namely TR10%, TR20% and TR40%, received 10, 20 and 40% aqueous extract of the bark of T. ramosissima, respectively. Both aqueous extracts of bark and burned bark of T. ramosissima exhibited significant inhibitory effects against E. Thefloccosum and T. verrucosum. MICs of aqueous extracts of bark and burned bark were 15 and 30 mg/ml against bothT. verrucosum and E. floccosum, respectively Lesions were improved in TR20%, TR40% and PC groups compared with NC group. The clinical efficacy in TR10%, TR20%, TR40%, and terbinafine groups were 15.84, 47.4, 78.96, 73.7% compared with NCgroup, respectively. Phytochemical analysis of the bark indicate the presence of flavonoids, alkaloids, condensed tannins, coumarins, saponins, triterpenes, steroids, cardiac glycosides and anthocyanines. Our findings support the historical use of T. ramosissima for the treatment of tinea, and also indicate its potential as an antifungal phytomedicine.